A BRIGHTER TOMORROW: PRIORITIZING CHILD AND ADOLESCENT MENTAL HEALTH IN PAKISTAN - Abbas, Kiran; Dars, Jawed Akbar (Journal of Pakistan Psychiatric Society, 2023)
ABSTRACT There is a crucial need for recognising children and adolescents as an integral part of society, especially in a nation with a significant youth demographic. Pakistan’s 280 million population, includes 100 million youth, and require urgent investment in mental well-being, particularly addressing psychiatric disorders like depression and anxiety, especially for women, whose welfare is often neglected. At present, Pakistan has an alarming shortage of psychiatrists, with one of the lowest numbers in the WHO Eastern Mediterranean Region. Despite existing policies, there is a clear lack of tailored laws addressing the specific needs of children and adolescents. The efforts made by organisations like the College of Physicians and Surgeons Pakistan and Sindh Mental Health Authority are acknowledged, but nonetheless, there is a pressing need for a robust policy. The progress made by neighbouring countries in formulating and implementing mental health policies, particularly emphasising the importance of mental health within a holistic healthcare system, is noteworthy. An emphasis has been laid on the urgency of the situation, advocating for prompt action, comprehensive policies, and unwavering commitment. The proposed future directions include a call to actively prioritise the mental well-being of youth to shape a brighter future for Pakistan.